On the selection of arbitrators - Geoffroy de Clippel; Kfir Eliaz; Brian Knight (Brown University, Department of Economics, 2012)
A key feature of arbitration is the possibility for conflicting parties to partake in the selection of the person who will rule the case. We analyze this problem of the selection of arbitrators from the perspective of implementation theory. Theoretical, empirical and experimental arguments are combined to highlight difficulties with a procedure that is commonly used in practice and to develop and identify better performing procedures.
Keywords: 330